Analysis of compliance to antiretroviral treatment among patients with HIV/AIDS - Hélia Carla de Souza; Márcio Rabelo Mota; Amanda Ribeiro Alves; Filipe Dinato Lima; Sandro Nobre Chaves; Renata Aparecida Elias Dantas; Samuel Barbosa Mezavila Abdelmur; Ana Paula Vaz da Silva Mota
ABSTRACT Objective: To analyze the compliance to antiretroviral therapy among HIV/AIDS patients. Method: 99 HIV-positive volunteers undergoing treatment responded to a semi-structured sociodemographic interview and to a questionnaire that assessed compliance to antiretroviral treatment. Results: In the sample analyzed, 52.5% of the volunteers presented good/adequate treatment compliance, while 33.3% presented low/insufficient compliance. There was no significant difference between men and women in the questionnaire score, nor between groups with different levels of education. Conclusion: The main items of the questionnaire that contributed to good/adequate compliance were: positive impact of treatment on health and quality of life, few side effects after initiation of therapy, and positive self-evaluation of participants regarding their compliance to antiretroviral therapy. The main barriers detected for compliance to antiretroviral therapy were the lack of knowledge about current medications and the lack of information on antiretroviral therapy drugs.